A Theoretical Model of Sequential Combinatorial Games of Subsidies and Penalties: From Waste to Renewable Energy - Dou, Yijie; Zhang, Tong; Meng, Xin (Frontiers in Energy Research, 2021)
Subsidies and penalties are two main regulation methods adopted by authorities to promote the development of renewable energy. Due to the possibility of subsidy fraud, it is necessary to explore the effective ways to combine these two policies. In this paper, subsidy and penalty policies are incorporated into a sequential game theory model to explore the impact of different regulatory mechanisms on the promotion of renewable energy from recycled resources. We take biodiesel production from used cooking oil (UCO) as an example. UCO can be made into either environmental-friendly biodiesel or mixed into fresh cooking oil, resulting in inferior cooking oil containing harmful carcinogens but with huge profits. There are two mechanisms in the sequential combination model, spot checks after subsidy or subsidy after spot checks. Under both cases, fines are imposed if fraud is found during spot checks. The amounts of subsidies and fines also need to be determined. We show that the effects of subsidies depend on the implementation of the timing. The ex-ante subsidies have no effect. When spot checks are performed first, the larger subsidies will increase the probability of producing inferior cooking oil due to lower probability of spot checks. While combined with penalties, the ex-post subsidies have a positive effect on biodiesel production. That is, there exists synergy effect of penalty and subsidy on renewable energy production. In an infinitely repeated game, the shutdown threat of a grim-trigger strategy (GTS) is much easier to induce biodiesel production than the penalty threat of a tit-for-tat strategy (TFT). When penalties are large enough, TFT can achieve the same goal of legal production effectively as GTS. The sooner illegal production is observed, the lower penalties required to induce the processor to produce legally. Comparing to subsidies, penalties are more effective in encouraging processors to produce renewable energy rather than illegal products. Moreover, our simulation results suggest that higher fines or profits from legal production are more likely to stimulate renewable energy production than subsidies. Our findings enrich our knowledge of the link between government regulations and the promotion of renewable energy.